2011
DOI: 10.1038/ismej.2011.20
|View full text |Cite
|
Sign up to set email alerts
|

Carbon, nitrogen and O2 fluxes associated with the cyanobacterium Nodularia spumigena in the Baltic Sea

Abstract: Photosynthesis, respiration, N 2 fixation and ammonium release were studied directly in Nodularia spumigena during a bloom in the Baltic Sea using a combination of microsensors, stable isotope tracer experiments combined with nanoscale secondary ion mass spectrometry (nanoSIMS) and fluorometry. Cell-specific net C-and N 2 -fixation rates by N. spumigena were 81.6±6.7 and 11.4 ± 0.9 fmol N per cell per h, respectively. During light, the net C:N fixation ratio was 8.0 ± 0.8. During darkness, carbon fixation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
118
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(128 citation statements)
references
References 47 publications
9
118
1
Order By: Relevance
“…These respiration rates were similar to those in August 2009 and 2011, when dark respiration varied between 0.038 and 87 nmol O 2 h À 1 in Nodularia colonies with diameters from 0.3 to 5.0 mm (see also Ploug et al, 2011). Many aggregates of N. spumigena held interior anoxia because of their size, high respiration rates and their compact structure.…”
Section: Resultssupporting
confidence: 76%
“…These respiration rates were similar to those in August 2009 and 2011, when dark respiration varied between 0.038 and 87 nmol O 2 h À 1 in Nodularia colonies with diameters from 0.3 to 5.0 mm (see also Ploug et al, 2011). Many aggregates of N. spumigena held interior anoxia because of their size, high respiration rates and their compact structure.…”
Section: Resultssupporting
confidence: 76%
“…Extensive blooms of Trichodesmium occur in the tropical ocean, whereas the genera Nodularia and Aphanizomenon bloom in brackish waters, and Aphanizomenon in lakes (Capone, et al, 1997;Ibelings and Maberly, 1998;Larsson et al, 2001). These N 2 -fixing cyanobacteria form colonies and leak a substantial fraction of newly fixed N 2 to the surrounding water (Mulholland and Capone 2001;Ploug et al, 2010Ploug et al, , 2011. However, quantitatively little is known about the fate of this newly fixed nitrogen, its role for the microbial and classical food webs and for large-scale biogeochemical fluxes (Mulholland, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the Baltic Sea, it is has been shown that ca. 40-80% of the fixed nitrogen is released as dissolved bioavailable nitrogen for redistribution in the food web (Ohlendieck et al, 2007;Wannicke et al, 2009Wannicke et al, , 2013Ploug et al, 2011). Larsson et al (2001) have estimated that N 2 -fixation in the Baltic Sea Proper is 180-430 kt N year −1 , and this amount would be sufficient to sustain 30-90% of the pelagic net community production during summer.…”
Section: Introductionmentioning
confidence: 99%